Factors that affect the menarche and the menstrual process: socio-economic level and physical activity - Delgado Villa, Renée (1989)
It reviews the publications related with sexual maturity process and factors that, in some way, affect it. It studies a population of 1570 women from Lima and 189 from Arequipa, of different socioeconomic level, with ages from 12 to 48 years. The results allow the assertion that the socioeconomic level -that it is expressed in the nutritional state- is a fundamental factor in the sexual maturity process and the reproductive function. The secular trend to an earlier age of menarche has not yet arrived to the point expected due to the genetic factor. The results are compared with those of a north european women's population. It shows that moderate physical activity improves the reproductive function and that, to the present time, the age of menarche is earlier - or at least not lates- in Arequipa then in Lima City. These results put on second place the importance of the geographic altitude in relation to other factors, at least when we talk about habitable middle altitudes.